Potency Adjusted Generic Versions of Argatroban Can Be Differentiated from Branded Argatroban in Thrombin Generation and Platelet Activation Assays - (:unkn) unknown (THIEME MEDICAL PUBL INC, 2008)
Argatroban is an antithrombin (AT) drug approved by the U.S. Food and Drug administration for the anticoagulation of patients with heparin-induced thrombocytopenia (HIT) and for patients at risk of HIT undergoing percutaneous coronary intervention. Three generic versions of argatroban (gartban, slovastan, and argaron) are now available. In this study, the anticoagulant bioequivalence of the generic and branded argatrobans were compared using whole blood, platelet-rich plasma, platelet-poor plasma, and antithrombin-deficient plasma using, clot-based assays. In addition, biochemical systems related to hemostatic mechanisms that involve thrombin were employed, Including thrombin generation, factor Xa generation, platelet activation, fibrinokinetics, and activation of thrombin activatable fibrinolytic inhibitor. Overall, the order of potency was gartban > slovastan > argatroban = argaron; however, the degree of potency differed by assay. Moreover, the inhibition of thrombin by each drug resulted in different mechanisms, as demonstrated in assays dependent on thrombin for enzymatic activation. These data demonstrate that equivalency of generic argatrobans cannot be determined based on their activity in a single clot-based assay. Clinical trials are warranted to evaluate the safety and efficacy of the generic argatroban drugs before use in patients.
Keywords: Argatroban; thrombin inhibitors; generic; anticoagulant; safety; HEPARIN-INDUCED THROMBOCYTOPENIA; ECARIN CLOTTING TIME; RECOMBINANT HIRUDIN; ANTICOAGULANT; INHIBITOR; THERAPY; INVITRO; NO-805